2020
DOI: 10.1128/msystems.00296-20
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Analysis of Cystic Fibrosis Sputum and Saliva Reveals Overlapping Communities and an Opportunity for Sample Decontamination

Abstract: ABSTRACT Culture-independent studies of the cystic fibrosis (CF) airway microbiome typically rely on expectorated sputum to assess the microbial makeup of lower airways. These studies have revealed rich bacterial communities. There is often considerable overlap between taxa observed in sputum and those observed in saliva, raising questions about the reliability of expectorated sputum as a sample representing lower airway microbiota. These concerns prompted us to compare pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Third, our observation of a consistent retention of specific non-pathogen taxa across multiple models (with and without the addition of potentially confounding EMR features, including age and BMI) points to the potential for a distinct causal pathway that is orthologous to age or BMI. We note that the interpretation that oral bacteria are active players in the lung environment is further buttressed by a recent study on people with established CF disease (Lu et al 2020) that used paired sputum and saliva samples to infer the presence of substantial populations of oral bacteria in the lung.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, our observation of a consistent retention of specific non-pathogen taxa across multiple models (with and without the addition of potentially confounding EMR features, including age and BMI) points to the potential for a distinct causal pathway that is orthologous to age or BMI. We note that the interpretation that oral bacteria are active players in the lung environment is further buttressed by a recent study on people with established CF disease (Lu et al 2020) that used paired sputum and saliva samples to infer the presence of substantial populations of oral bacteria in the lung.…”
Section: Discussionmentioning
confidence: 97%
“…Under this contamination model, increasing pathogen load compared to a constant background of oral microbiome contamination generates a spurious link between oral microbes, microbiome diversity, and patient health [27]. While recent paired sputum-saliva sampling analysis indicates that oral sample contamination is not a substantial contributor to sputum microbiome profiles in people with established CF lung disease [29], these conflicting hypotheses highlight the uncertainty in the role specific taxa present in sputum.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies are needed to quantify the total bacterial load by qPCR to determine the differences in absolute bacterial load of total and specific bacteria between groups of different clinical status in COPD. Of note, although sputum has been widely used to study the lung microbiome, considerable overlap between sputum microbiome and saliva microbiome has been observed [19]. As negative correlation between oral hygiene on COPD has been reported [20,37], the spatial dynamics between upper and lower respiratory tract microbiome and the potential roles of these oral microbiome in COPD development in the Chinese population is highly desired.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is prone to oral microbiome contamination given the topological continuity of the oral cavity and the lower respiratory tract, sputum has been widely used as a surrogate to study the lung microbiome in different respiratory diseases [19,20]. The objectives of this study were to characterize the AECOPD sputum microbiome in a Chinese population and to determine whether specific sputum microbiome biomarkers could be identified in order to differentiate eosinophilic from other subtypes of AECOPD.…”
Section: Introductionmentioning
confidence: 99%
“…A number of approaches to address the sputum contamination issue have been taken, including mouth cleaning and sputum rinsing 29 , as well as more invasive sampling techniques (subject to clinical need 28,[30][31][32] ). Most recently, computational analysis of paired sputum and saliva samples from adults with established CF lung disease has demonstrated that saliva contamination during sample collection has a minimal quantitative impact on the community profile 33 .…”
Section: Introductionmentioning
confidence: 99%